Accessing land in the city s peri-urban areas: The case of Lilongwe, Malawi - Galimoto, McDonald (School of Architecture, Planning and Geomatics, 2025)
Land access is arguably key to the attainment of sustainable urbanisation and development. Studies show that high urbanisation rates have resulted in a high demand for serviced land and housing in the face of a slow rates of formal provision of the same. This is particularly true in Lilongwe's peri-urban areas where, despite presenting itself as an opportunity to facilitate a parallel system of accessing land for the majority of residents, the unrelinquished customary land tenure system in the urban and periurban areas is continuously in conflict with the failing statutory land tenure. Therefore, the study asks: How do Lilongwe's residents access land in the city's peri-urban areas? This qualitative case study research sourced primary data through semi-structured individual interviews with residents in Areas 26, 44, 54 and 55 and non-participant observations as well as secondary data sourced through desktop investigation. The findings show that, despite being the preferred mechanism, the formal land access system is marred with numerous challenges emanating from the historicised internal and external inefficiencies which culminate in the government's delayed creation of plots. The challenges include limited human, technical and financial capacity and inconsistent application of the law. These inefficiencies and challenges are rooted in Malawi's historical land dispensation that favours clientelist modes of political legitimation that manifest in poorly coordinated land expropriation programmes and l'aissez faire implementation of planning law. These inefficiencies have led to the proliferation of the uncharted (read informal) mechanisms of land access. The findings also indicate that land access remains gendered, by the prevailing inheritance rules in each area, which is observed to be changing due to intermarriages, modernisation and legal reforms. By declaring customary land as planning areas without instituting legal procedures to formally extinguish the existing customary land tenure rights, the state and non-state actors disregard international human rights principles, protocals, treaties and conventions. These findings echo scholarship that finds land tenure systems in the global South cities to be precarious. Despite strong commitments, in recent times, to implement urbanisation-focussed SDG 11 “Make cities and human settlements inclusive, safe, resilient and sustainable”, the empirical evidence and the historicised trends observed in Lilongwe entails 2030 may come too quickly for Malawi to comprehensively achieve the goal. Based on these findings, the research recommends avenues for future research that will inform the government's land access and tenure formalisation programmes in the peri-urban areas.